Vitamin B12 (hydroxocobalamin) administration in the management of persistent vasoplegic shock - Jibran Ikram; Cassandra L. Williams; Aariya Srinivasan; Jose L. Diz Ferre; Sabry Ayad (Saudi Journal of Anaesthesia)
Vasoplegia, characterized by low systemic vascular resistance despite normal to high cardiac output, can result from various conditions, including cardiac surgery, and progress to vasoplegic shock if untreated. This case study involves a male in his 70s with multiple risk factors, including a left ventricular ejection fraction of 35%, who developed vasoplegia after taking lisinopril on the day of his elective coronary artery bypass graft (CABG) surgery. Despite initial management with vasopressors, the patient’s condition necessitated postponing the CABG. The patient was stabilized in the ICU with a combination of vasopressin, epinephrine, norepinephrine, and hydrocortisone, and his vasoplegia was successfully treated with hydroxocobalamin, leading to significant clinical improvement. The patient later underwent a successful CABG without preoperative ACE inhibitor use. This case underscores the potential of hydroxocobalamin as an effective treatment for vasoplegia, particularly following ACE inhibitor use in cardiac surgery patients.